Technological approaches to aqueous extraction of phenolic compounds from Plectranthus Ornatus: antioxidant potential and toxicological assessment - Evangelista, Larissa Ben; Sartori, Valdirene Camatti; Touguinha, Luciana Andrade; Branco, Cátia Santos; Salvador, Mirian (Disciplinarum Scientia | Naturais e Tecnológicas, 2025)
Plectranthus ornatus Codd is a species of the genus Plectranthus, popularly known as “Boldo”. In traditional medicine, its leaves are commonly prepared as tea, either by infusion or decoction. The species of the genus Plectranthus are rich in secondary metabolites; however, studies on the phenolic composition and biological activities of P. ornatus are scarce. This study aimed to produce aqueous extracts from leaves of P. ornatus through different methods (decoction, infusion, reflux, and freeze-dried) and evaluate their antioxidant activity by the 2,2-diphenyl-1-picrylhydrazyl (DPPH•) method, the content of total phenolic compounds by Folin Ciocalteu, and in vivo toxicity using Artemia salina. Antioxidant activity was expressed as IC50, with the best result obtained for the lyophilized extract (6.85 ± 0.60 mg/mL). The same was found for total phenolic content (23.21 ± 0.60 mg gallic acid equivalents/g). All processes showed a strong positive correlation (r>0.9; p<0.05) between total phenolic content and antioxidant activity. The lyophilized aqueous extract was non-toxic to Artemia salina at all tested concentrations. These findings highlight the importance of extraction technology in optimizing the bioactive potential of P. ornatus, reinforcing its potential as a safe and effective natural antioxidant source.